Modulation of the Left Prefrontal Cortex with High Frequency Repetitive Transcranial Magnetic Stimulation Facilitates Gait in Multiple Sclerosis - Amer M. Burhan; Priya Subramanian; Luljeta Pallaveshi; Brittany Barnes; Manuel Montero-Odasso (Case Reports in Neurological Medicine)
Multiple Sclerosis (MS) is a chronic central nervous system (CNS) demyelinating disease. Gait abnormalities are common and disabling in patients with MS with limited treatment options available. Emerging evidence suggests a role of prefrontal attention networks in modulating gait. High-frequency repetitive transcranial magnetic stimulation (rTMS) is known to enhance cortical excitability in stimulated cortex and its correlates. We investigated the effect of high-frequency left prefrontal rTMS on gait parameters in a 51-year-old Caucasian male with chronic relapsing/remitting MS with residual disabling attention and gait symptoms. Patient received 6 Hz, rTMS at 90% motor threshold using figure of eight coil centered on F3 location (using 10-20 electroencephalography (EEG) lead localization system). GAITRite gait analysis system was used to collect objective gait measures before and after one session and in another occasion three consecutive daily sessions of rTMS. Two-tailed within subject repeated measure t-test showed significant enhancement in ambulation time, gait velocity, and cadence after three consecutive daily sessions of rTMS. Modulating left prefrontal cortex excitability using rTMS resulted in significant change in gait parameters after three sessions. To our knowledge, this is the first report that demonstrates the effect of rTMS applied to the prefrontal cortex on gait in MS patients.